Retinal Diseases and Parkinson Disease: A Population-Based Study - Chen, Po-Chih; Chung, Chen-Chih; Cheng, Yun-Yung; Chen, Wan-Ting; Hong, Chien-Tai; Chan, Lung; Chien, Li-Nien (Frontiers in Neuroscience, 2021)
IIntroduction: Patients with Parkinson disease (PD) tend to have ophthalmic symptoms. Retinal diseases are associated with central nervous system diseases, especially neurodegenerative diseases. Here, we investigated the association of retinal diseases with PD, especially the temporal relationship before and after PD diagnosis. Methods: Data were obtained from the National Health Insurance Research Database of Taiwan. In total, 21,845 patients with newly diagnosed PD were matched with four controls each on the basis of propensity score. This study was bidirectional. A case–control study evaluated the adjusted odds ratio (aOR) of retinal disease before PD diagnosis by using conditional logistic regression. Furthermore, a cohort study evaluated the adjusted subdistribution hazard ratio (aSHR) for new-onset retinal and optic nerve diseases after PD diagnosis by using competing risk analysis. The association between PD with optic nerve diseases and glaucoma (another common ophthalmic diseases with the consequence of retinal dysfunction) were also analyzed as reference. Results: In the case–control study, PD was found to be significantly comorbid with recent and remote retinal disease (recent: ≤5 years, aOR: 1.12, 95% confidence interval [CI]: 1.03–1.23; remote: >5 years, aOR: 1.18, 95% CI: 1.04–1.34). No similar association was identified between optic nerve disease or glaucoma with PD. In the cohort study, patients with PD were found to have a low risk of retinal disease in short-term (≤5 years, aSHR: 0.81, 95% CI: 0.71–0.93) and long-term (>5 years, aSHR: 0.82, 95% CI: 0.72–0.93) follow-up. Conclusions: The study findings demonstrated that patients with prediagnostic PD were at greater risk of retinal disease than non-PD participants, but the risk reversed afterwards. Thus, retinal disease may be a premotor manifestation of PD, and there may be some possible effect of dopamine supplements on retina.